A SIMPLIFIED METHODOLOGY FOR MAPPING GROUNDWATER VULNERABILITY AND CONTAMINATION RISK, AND ITS FIRST APPLICATION IN A TROPICAL KARST AREA, VIETNAM - Nguyet V.T.M.; Goldscheider N. (My University, 2006)
A simplified methodology for mapping groundwater vulnerability and contamination risk is proposed, and the first application of the methodology, in a mountainous tropical karst area, is presented. The test site is the Tam Duong area, one of the poorest and remotest regions in northern Vietnam. The methodology requires a minimum of input data, which makes it particularly useful for developing countries. Vulnerability is assessed on the basis of two factors, which take into account the duality of recharge processes in karst aquifer systems: the overlying layers (O) and the concentration of flow (C). The risk map is obtained by putting together the vulnerability map and a simplified hazard assessment. The resulting maps provide a basis for groundwater protection zoning and land-use planning. Tracer tests and microbiological data confirmed the vulnerability and risk assessment in the test site.
Keywords: GROUNDWATER VULNERABILITY; CONTAMINATION RISK; TROPICAL KARST AQUIFER; DEVELOPING COUNTRY; SOCIO-ECONOMIC ASPECTS